Biology Learners’ Conception of Ecology of a Wetland Ecosystem - Tenane Makabelo; Mokuku Tsepo (Discourse and Communication for Sustainable Education)
Wetlands ecosystems play an important role and are relevant to biotic and abiotic factors including survival of humans. Therefore, it is imperative that learners in Lesotho become sensitized to the knowledge about the ecology of wetland ecosystems. Few studies investigated Lesotho students’ ecological literacy of wetlands hence this study explored biology learners’ knowledge of that topic. The research was conducted using a mixed research approach and data was collected using observation and close-ended questionnaires. This research approach neutralized the weaknesses of data and strengthened the validity of the research findings. The ecological literacy has been adopted as a theoretical framework. The research findings revealed that most participants had moderate ecological knowledge of a wetland ecosystem and students’ conceptions were mostly based on their cultural background not much from class teaching. Findings also revealed that boys were more ecologically literate than girls. For further research, higher order levels of Bloom’s taxonomy could be tested by using other different research tools and teachers’ approaches in teaching of ecological concepts.